Creating a Transdisciplinary Research Center to Reduce Cardiovascular Health Disparities in Baltimore, Maryland: Lessons Learned - Cooper, Lisa A. (American Public Health Association, 2013)
Cardiovascular disease (CVD) disparities continue to have a negative impact on African Americans in the United States, largely because of uncontrolled hypertension. Despite the availability of evidence-based interventions, their use has not been translated into clinical and public health practice. The Johns Hopkins Center to Eliminate Cardiovascular Health Disparities is a new transdisciplinary research program with a stated goal to lower the impact of CVD disparities on vulnerable populations in Baltimore, Maryland. By targeting multiple levels of influence on the core problem of disparities in Baltimore, the center leverages academic, community, and national partnerships and a novel structure to support 3 research studies and to train the next generation of CVD researchers. We also share the early lessons learned in the center’s design.